EVALUATION OF COLLECTION SAMPLES OF VEGETABLE BEANS (PHASEOLUS VULGARIS L.) FOR ECONOMICALLY VALUABLE GROUNDS IN THE CONDITIONS OF THE MOSCOW REGION - Sh. Anton; A. M. Smirnova; A. A. Antoshkin (Овощи России, 2018)
As part of working on the solution of the task of importing asparagus beans, it is necessary to create a conveyor of green beans for vegetables during the growing season under the conditions of the Central Nonchernozem Zone (CNZ). In this regard, in 2018, work was continued on the evaluation of the existing collection of the FSBSI FSVC on economically valuable grounds, which allowed pre-select promising samples for further breeding work. According to the results of the assessment of the collection variety samples of vegetable beans in 2018, 30 variety samples of different groups of ripeness were identified as initial forms for breeding work on creating varieties that meet the requirements of the processing industry and creating a conveyor for producing asparagus products in the CNZ. Selected varieties are described and evaluated for the productivity of beans and seeds, suitability for mechanized harvesting, quality of the bean, seed size, resistance to the most harmful diseases. It is important to note that the year 2018 was unfavorable for the optimal development of culture due to the negative weather conditions that developed from the 3rd decade of May to the 2nd decade of June. This has made its own adjustments to the development of plants, as a result of which the assessment on some grounds is not indicative.